THE IMPORTANCE OF LINKING WORDS IN ACADEMIC WRITING - Nurmaxmatova Firuza Rasulovna, (TADQIQOTLAR, 2026)
Abstract: Linking words, also called cohesive devices or transition markers, are important tools in academic writing. They help readers follow arguments, create logical links between ideas, and improve the overall flow of the text. This article looks at the types, functions, and significance of linking words in English academic writing. Based on the linguistic theories of cohesion and coherence by M. A. K. Halliday and Ruquaiya Hasan,  the  study  shows  that  using  linking  words  effectively  enhances  clarity, readability, and the overall quality of academic writing. Examples from student essays and research articles illustrate how to apply these devices in practice.